The Future of Management Theory: A Review of the Literature on Innovation, Sustainability, and Transformative Leadership - Manurung, Gerson; Hendayana, Yayan (Dinasti International Journal of Management Science, 2025)
In the face of global uncertainty and increasingly complex business dynamics, innovation, sustainability and transformative leadership are three key pillars that are indispensable in the development of future management theory. This research aims to explore the integration of these three elements in management theory, as well as to identify gaps in the existing literature related to this topic. The main question to be answered is how innovation, sustainability, and transformative leadership can support each other and form an adaptive managerial framework in the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era. The method used is a qualitative approach with in-depth literature analysis of previous research and relevant theoretical studies. The results showed that there is a significant relationship between the three elements in forming a more adaptive and sustainable managerial model. The research also found that there are still gaps in the integration of the three elements in one managerial framework, as well as a lack of longitudinal and cross-cultural studies. The conclusion of this study is that future management theory development should pay attention to a holistic approach that integrates innovation, sustainability, and transformative leadership. Future research is recommended to develop case study-based integrative models and explore the role of technology in shaping new leadership.